2017
DOI: 10.1371/journal.pone.0185895
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of longitudinal faculty development programs on MCQs items writing skills: A follow-up study

Abstract: This study examines the long-term impact of the faculty development programs on the multiple choice question (MCQ) items’ quality leading to study its effect on the students’ overall competency level during their yearly academic assessment. A series of longitudinal highly constructed faculty development workshops were conducted to improve the quality of the MCQs items writing skills. A total of 2207 MCQs were constructed by 58 participants for the assessment of 882 students’ cognitive competency level during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 41 publications
4
44
0
3
Order By: Relevance
“…and not based at the university with training workshops and suggests a range of theoretically informed practical strategies (see Table 2). However, there is significant evidence that faculty development programs do improve item quality in medical school examinations [2,[29][30][31][32][33]. Moreover, studies adopting an SDT analysis such as Lyness et al have previously highlighted the importance of supporting the development of skills necessary to meet the tasks given to medical academics [18].…”
Section: Discussionmentioning
confidence: 99%
“…and not based at the university with training workshops and suggests a range of theoretically informed practical strategies (see Table 2). However, there is significant evidence that faculty development programs do improve item quality in medical school examinations [2,[29][30][31][32][33]. Moreover, studies adopting an SDT analysis such as Lyness et al have previously highlighted the importance of supporting the development of skills necessary to meet the tasks given to medical academics [18].…”
Section: Discussionmentioning
confidence: 99%
“…But, unlike to such result, Baig et al, in 2014 found that there is necessitate for revising the quality of the MCQs test content by the program team because it is frequently not credible. [41,42] Parallel to this study finding, recently, in a research study in Egypt by Nassar in 2017 who reported that the high-quality MCQs is needed for undergraduate student's assessment in healthcare sciences. MCQs tests should be assessed and adjusting of any pitfalls or flaws.…”
Section: Discussionmentioning
confidence: 55%
“…We suggest that MC questions with a random number of right answers increase the power of the MC to assess the knowledge of students and might also offer the chance to improve their problem-solving skills and in other words make it possible to reach higher levels in Bloom's taxonomy, indeed at least in the US biology teaching to undergraduates even higher Bloom levels of knowledge were measurable with MCQ [24]. Others complained that at least in tests being given to first-and second-year medical students, only low competence levels were used and called for improving the MCQ by offering faculty programs on MCQ writing skills [25,26].…”
Section: Discussionmentioning
confidence: 99%